Hubungan Tingkat Konsumsi Junk Food dengan Obesitas pada Anak Usia Sekolah - Khansa Cantika Indraguna; Iis Aisyah; Ahmad Purnama Hudaya (Jurnal Keperawatan Florence Nightingale, 2024)
Global changes in food consumption patterns are driven by technology and globalization, guiding the popularity of instant foods such as burgers, pizza and nuggets. The occurrence of metabolic syndrome is associated with food intake, this is thought to be related to a person's lifestyle. Metabolic syndrome is experiencing an exponential increase in obesity worldwide. This study aims to investigate the relationship between consuming junk food and obesity in school-aged children. This research utilizes a correlational survey design and applies a cross-sectional approach, namely with an analytical design, the research sample uses a total sampling technique, involving 70 students in grades 5 and 6 in the age range 10 to 12 at SD Negeri Bendungan II as respondents. The incidence of obesity in students at SD Negeri Bendungan II was 16 students (22.9%), using statistical test analysis, using chi-square resulted in a p-value of 0.018. (p-values ??< 0.05) therefore H0 was rejected and H1 was accepted with the conclusion that there was a link or relationship between the level of consumption of junk food and the incidence of obesity in grade 5 and 6 students at SD Negeri Bendungan II.